Effect of Different Types of Upper Instrumented Vertebrae Instruments on Proximal Junctional Kyphosis Following Adult Spinal Deformity Surgery: Pedicle Screw versus Transverse Process Hook - Akira Matsumura; Takashi Namikawa; Minori Kato; Shoichiro Oyama; Yusuke Hori; Akito Yabu; Noriaki Hidaka; Hiroaki Nakamura (Asian Spine Journal, 2018)
Study Design Retrospective comparative study. Purpose To compare the incidence of proximal junctional kyphosis (PJK) between transverse process hooks (TPHs) and pedicle screws (PSs) at the upper instrumented vertebrae (UIV) following adult spinal deformity (ASD) surgery. Overview of Literature The choice of UIV implant type may be important for avoiding PJK; however, few comparative clinical studies have evaluated the incidence of PJK according to the type of UIV implant used in ASD surgery. Methods We retrospectively reviewed 39 consecutive patients with ASD (mean age, 67 years; mean follow-up period, 41 months) who underwent corrective surgery between 2009 and 2013. TPH was used in 17 patients and PS in 22 patients. PJK was defined as the presence of a UIV or UIV±1 fracture, or a change in the proximal junctional angle (PJA) of >20°. Data of patients with TPH and PS were compared. Results The TPH group had a PJK incidence of 17.6% compared with 27.3% in the PS group (p =0.47). In the TPH group, PJK was a result of UIV fracture in one patient, UIV−1 fracture in one patient, and ligamentous failure in one patient. In the PS group, six patients developed PJK because of UIV fracture. No differences in radiographic parameters were found between the two groups. After analyzing the PJA data in the patients with PJK, the changes in PJA were significantly higher in the PS group than in the TPH group (19.0°/5.0°, p =0.04). Conclusions Our results show that using TPH as a UIV implant may not prevent PJK; however, using TPH as the UIV anchor may prevent vertebral collapse if cases of UIV fracture. The increased risk of UIV fracture collapse in the PS group may be a result of a higher mechanical load on UIV when using PS.